Analisis Keberhasilan Sistem Informasi Pelayanan Publik Berbasis Online di Kota Bandung - Anggraeni Cahyaningrum, Firlly; Sufianti, Ely; Sodik Sudrajat, Achmad; Mustika Ramdani, Endah (Jurnal Ilmu Administrasi Negara, 2025)
This study aims to analyze the success of online-based public service systems in Bandung City and formulate recommendations for improvement. Issues identified include low ratings for the Lapor!, Gampil, and Bandung Sadayana applications, as well as slow data updates on the Open Data portal. The method used is quantitative descriptive through questionnaires, documentation, and interviews. The results indicate that the usage dimension received the lowest score, indicating that service utilization remains low. Meanwhile, the system quality dimension received the highest average score, indicating that users' perceptions of the system are generally positive. The Gampil application received the highest satisfaction rating (87.61%), while Salaman received the lowest (69.72%). In conclusion, online public services in Bandung City are considered suboptimal because they are technically adequate but underutilized. These results are important as a basis for evaluating the city government's digital policies. Based on these findings, it is recommended to educate the public about all online public services and develop application features based on real community needs to make services more effective and inclusive.